2022
DOI: 10.1039/d2nj00310d
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly functionalization of hexagonal boron nitride nanosheets with carbon dots towards reinforcement of the protective performance of water-borne epoxy coatings

Abstract: As a structural analogue of graphene, hexagonal boron nitride (h-BN) is getting increased attention in anticorrosive polymer coatings due to its electrical insulation and high barrier properties. However, the hydrophobicity...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…This suggests that PEI-BNNSs are more effective at impeding the charge transfer process caused by corrosive substances’ infiltration compared to h-BN, thus providing long-term corrosion resistance for Q235 steel. As summarized in Figure d, the 0.5 wt % PEI-BNNSs/WEP composite coating is better than those of other previous BNNS/epoxy composite coatings. The PEI-BNNSs as excellent anticorrosive nanofillers in WEP coating have some advantages by comparing with different 2D fillers, including graphene, graphene oxide, and h-BN. The superb anticorrosive property is ascribed to the presence of PEI, which not only promotes uniform dispersion but also strengthens the interaction between BNNSs and WEP. This serves as an additional factor contributing to the coating’s outstanding corrosion resistance.…”
Section: Resultsmentioning
confidence: 96%
“…This suggests that PEI-BNNSs are more effective at impeding the charge transfer process caused by corrosive substances’ infiltration compared to h-BN, thus providing long-term corrosion resistance for Q235 steel. As summarized in Figure d, the 0.5 wt % PEI-BNNSs/WEP composite coating is better than those of other previous BNNS/epoxy composite coatings. The PEI-BNNSs as excellent anticorrosive nanofillers in WEP coating have some advantages by comparing with different 2D fillers, including graphene, graphene oxide, and h-BN. The superb anticorrosive property is ascribed to the presence of PEI, which not only promotes uniform dispersion but also strengthens the interaction between BNNSs and WEP. This serves as an additional factor contributing to the coating’s outstanding corrosion resistance.…”
Section: Resultsmentioning
confidence: 96%
“…In the Bode plots (Figure S13), regardless of the exposure time, the LBNC shows the highest impedance modulus. The results confirm that the LBNC can provide the best protection for the underlying substrates. , The EIS plots were then fitted through equivalent electric circuit models (see Figure S14) to further interpret the corrosion behaviors, and the detailed parameters are recorded in Table S4. The coating resistance ( R c ) can reflect the corrosion protection of the coatings.…”
Section: Resultsmentioning
confidence: 99%
“…This study brought a new approach to corrosion mechanisms regarding the surface morphology and surface area of the barrier material. Subsequently, 2D boron nitride nanosheets (BNNS) have been explored for anticorrosion applications. Compared to traditional micron-sized irregular BN particles, 2D BNNS’s large lateral dimension offers greater interfacing with the host material, increasing the corrosion resistance in such systems. Yi et al, in their study on size-selected BNNS coating on a polymer, concluded that larger BNNS (∼21.4 μm 2 ) greatly enhanced the corrosion resistance of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Bulk, free-standing 1D boron nanotubes (BNNTs) fabricated as 100% BNNT and oriented randomly in-plane are commercially available as BNNT buckypaper (BP). They are analogous to carbon nanotubes but offer multifunctional advantages, including piezoelectricity, electrical insulation, high-temperature stability, and neutron absorption. , Compared to 2D hBN nanoplatelet (BNNP), 1D BNNT is arranged randomly into a porous 3D structure and offers a substantially greater surface area. Previous research studies concluded that hBN with a high surface area offers increased corrosion resistance due to higher interfacing with the underlying material. Yet, BNNTs are not recognized as corrosion-inhibiting additives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation